Data structures via C++ - Berman, A. Michael (Oxford University Press, 1997)
Bringing together the fundamental topics of a traditional introductory data structures course and the current world of C++ and object-oriented programming,Data Structures via C++: Objects by Evolution offers an evolutionary approach to the subject. It combines a sound pedagogy for teaching data structures at the introductory (CS2) level with modern ideas in software engineering and object-oriented programming. The book introduces students (and instructors) to C++ and object-oriented programming using a "just-in-time" approach which leads readers from traditional techniques to more current ideas